Lifting Plan for Containers Weight of 20 tons - Prasetya, Adhita; Komarudin, Udin; Santoso, Heru (International Journal of Psychosocial Rehabilitation, 2020)
Infrastructure development in Indonesia supporting economic activities has reached its highest point in 2019. The construction of elevated toll roads has become one of the solutions for the development of the Cikampek-Jakarta toll road. Based on information, there have been several accidents on the toll road project due to the failure of the lifting process using a mobile crane. Based on this, an example of planning the appointment of a 40-foot container with a load of 20 tons using a mobile crane is intended to provide lessons in transport planning so that accidents that occur can be minimized. The method used in this plan is as follows: (1) identify the dimensions and weight of the object to be transported; (2) determine the crane data to be used; (3) calculate the total load of the object to be lifted along with the lifting gear; (3) find the percentage of crane conditions used; (4) calculate the safety factor; (5) compare lifting capacity with the allowable lifting load based on the load card. Based on the calculation results, it can be concluded that the total load is 24,676 tons, the lifting location factor is 28,377 tons, the load chart is 29,88 tons, the safety factor is 1,052, with a boom length of 17.5 m, a lift angle of 39°, and the length of the main host is 5.9 m.